Antifungal Activity of Cassia alata L. Ethyl Acetate and N-Hexane Leaves Extract against Candida albicans - Muhammad Anugerah Alam Waris; Andi Muhammad Farid; Misra (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2021)
This study aims to determine the effect of Cassia alata L. ethyl acetate and n-hexane leaves extract in inhibiting the growth of Candida albicans. The study used an experimental laboratory. In this study, C. alata ethyl acetate and n-hexane leaves extract used with concentrations of 2% w/v, 4% w/v and 8% w/v. The results showed that ethyl acetate and n-Hexane extracts inhibit C. albicans growth at 2% w/v, 4% w/v and 8% w/v concentrations with diameters of 9 mm, 11 mm, 13 mm for ethyl acetate and 9.3 mm, 12 mm, 14 mm for n-hexane solvent.